Les « discours » de Veturia, Valeria et Hersilia - Emmanuelle Valette (Cahiers Mondes Anciens, 2013)
The analysis of the numerous narratives dedicated to the feminine embassy sent to Coriolan shows what makes the specific efficiency of the “matronal speech”. These narratives, written in Greek or in Latin, fit into a tradition and resort to diverse models to show the specificity of the feminine speech acts ; these models may be literary ones or they can be inspired by existing social practices. In the Livian version, the persuasive strength of Veturia’s speech (oratio), the mother of Coriolan, leans on the visual dimension of the picture she composes with the group of the women in mourning around her. But the poignant effect (movere) of her speech is also stressed by tears and collective lamentations of the matrons, an attitude evoking that of the Roman supplications. The narratives in Greek draw more from the tragic to build the figure of the “mother” and the “supplicant”. But the historic fiction of Coriolanus also resonates with the episode of the Sabine women who, by their words and prayers, knew how to convince their fathers and husbands to sign the peace. The exemplary value of this intervention creates a kind of “tradition of the exception”, which appears characteristic of the feminine action in Roman history.